Functional Specialization of Skin Dendritic Cell Subsets in Regulating T Cell Responses - Clausen, Björn E.; Stoitzner, Patrizia (Frontiers in Immunology, 2015)
Dendritic cells (DC) are a heterogeneous family of professional antigen presenting cells (APC) classically recognized as most potent inducers of adaptive immune responses. In this respect, Langerhans cells (LC) have long been considered to be prototypic immunogenic DC in the skin. More recently this view has considerably changed. The generation of in vivo cell ablation and lineage tracing models revealed the complexity of the skin DC network and, in particular, established the existence of a number of phenotypically distinct Langerin+ and negative DC populations in the dermis. Moreover, by now we appreciate that DC also exert important regulatory functions and are required for the maintenance of tolerance towards harmless foreign and self-antigens. This review summarizes our current understanding of the skin-resident DC system in the mouse and discusses emerging concepts on the functional specialization of the different skin DC subsets in regulating T cell responses. Special consideration is given to antigen cross-presentation as well as immune reactions towards contact sensitizers, cutaneous pathogens and tumors. These studies form the basis for the manipulation of the human counterparts of the murine DC subsets to promote immunity or tolerance for the treatment of human disease.